Renal sympathetic denervation improves myocardial apoptosis in rats with isoproterenol-induced heart failure by downregulation of tumor necrosis factor-α and nuclear factor-κB - Yao, Wei (Exp Ther Med, 2017)
Chronic congestive heart failure (CHF) is the end outcome of organic heart diseases and one of the major diseases harmful to human health. Renal sympathetic denervation (RSD) is the anatomical basis of transcatheter renal sympathetic nerve ablation within the renal artery. To date, the roles of norepinephrine and angiotensin II (Ang II) in myocardial apoptosis and their underlying mechanisms have not been well explored. The aim of the present study was to verify the hypothesis that RSD is likely to inhibit myocardial apoptosis by inhibiting the release of norepinephrine and Ang II. An isoproterenol-induced CHF rat model was established, and the effects of RSD on myocardial apoptosis were examined using flow cytometry and TUNEL staining. The expression of factors associated with myocardial apoptosis, including p53, tumor necrosis factor-α (TNF-α), nuclear factor-κB (NF-κB), caspase-2 and −3, were measured using quantitative polymerase chain reaction and western blot analysis. The results indicated that the mRNA levels of p53, TNF-α, NF-κB, caspase-2 and −3 were significantly reduced in the myocardial tissues of rats in the CHF+RSD group when compared with the levels in the CHF+sham group (P<0.01 for all). In addition, the protein levels of p53, TNF-α, NF-κB and caspases-2 and −3 were decreased by 42.6, 41.3, 46.7, 30.0 and 35.8%, respectively, in myocardial tissues of rats in the CHF+RSD group in comparison with the CHF+sham group (P<0.01 for all). Furthermore, myocardial apoptosis was improved in rats in the CHF+RSD group compared with that in the CHF+sham group (P<0.01). In conclusion, the present study provides a theoretical basis for application of RSD in the treatment of CHF.